Cell death regulation in myocardial toxicity induced by antineoplastic drugs - Yu, Xue; Yang, Yan; Chen, Tianzuo; Wang, Yuqin; Guo, Tianwei; Liu, Yujun; Li, Hong; Yang, Liming (Frontiers in Cell and Developmental Biology, 2023)
Homeostatic regulation of cardiomyocytes plays a critical role in maintaining normal physiological activity of cardiac tissue. Severe cardiotoxicity can lead to heart disease, including but not limited to arrhythmias, myocardial infarction and cardiac hypertrophy. In recent years, significant progress has been made in developing new therapies for cancer that have dramatically changed the treatment of several malignancies and continue to improve patient survival, but can also lead to serious cardiac adverse effects. Mitochondria are key organelles that maintain homeostasis in myocardial tissue and have been extensively involved in various cardiovascular disease episodes, including ischemic cardiomyopathy, heart failure and stroke. Several studies support that mitochondrial targeting is a major determinant of the cardiotoxic effects triggered by chemotherapeutic agents increasingly used in solid and hematologic tumors. This antineoplastic therapy-induced mitochondrial toxicity is due to different mechanisms, usually altering the mitochondrial respiratory chain, energy production and mitochondrial kinetics, or inducing mitochondrial oxidative/nitrosative stress, ultimately leading to cell death. This review focuses on recent advances in forms of cardiac cell death and related mechanisms of antineoplastic drug-induced cardiotoxicity, including autophagy, ferroptosis, apoptosis, pyroptosis, and necroptosis, explores and evaluates key proteins involved in cardiac cell death signaling, and presents recent advances in cardioprotective strategies for this disease. It aims to provide theoretical basis and targets for the prevention and treatment of pharmacological cardiotoxicity in clinical settings.